The Integrative Psychiatry Curriculum: Development of an Innovative Model - Noshene Ranjbar MD; Mari Ricker MD; Amelia Villagomez MD (SAGE Publishing, 2019)
The Integrative Psychiatry Curriculum (IPC) was developed to train psychiatry residents and fellows to apply an Integrative Medicine (IM) approach for patients presenting with psychiatric disorders. Launched in 2015, IPC includes interactive online courses, in-person experiential sessions, and a clinical component with supervision. Twenty-one residents and fellows have completed the curriculum. The purpose of the IPC is 2-fold: to enhance patient wellness through training residents and fellows in evidence-based whole-person care and to improve physician well-being through enhanced stress management and self-awareness utilizing the practice of mind-body skills within a supportive small group setting. Course participants are trained in a broad range of prevention and treatment options and learn about their evidence base; they then practice incorporating IM into diagnosis and treatment plans through supervised clinical experience. This article describes the development of IPC and its elements. Efforts are underway to further develop and standardize the offerings and increase the portability of the course, making it easier for Psychiatry training programs with limited faculty expertise in IM to provide the curriculum for residents and fellows. To reach the goal of disseminating such a curriculum for integrative psychiatry, further funding and collaboration with multiple residency training programs is needed.